2016
DOI: 10.1177/0018726715614073
|View full text |Cite
|
Sign up to set email alerts
|

Extending critical performativity

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractIn this article we extend the debate about critical performativity. We begin by outlining the basic tenets of critical performativity and how this has been applied in the study of management and organisation. We then address recent critiques of critical performance. We note these arguments suffer from an undue focus on intra-academic debates; engage in author-itarian theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(170 citation statements)
references
References 64 publications
(133 reference statements)
1
159
0
10
Order By: Relevance
“…That is, the goal of this kind of inquiry into motivation is to illuminate its complexities while highlighting questions and inspiring more inquiry and reflection. This might also offer novel avenues for engaging with motivation as a way to model an extended critical performativity (Spicer, Alvesson and Karreman, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…That is, the goal of this kind of inquiry into motivation is to illuminate its complexities while highlighting questions and inspiring more inquiry and reflection. This might also offer novel avenues for engaging with motivation as a way to model an extended critical performativity (Spicer, Alvesson and Karreman, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it is studied by means of cognitive approaches (Handley, Sturdy, Fincham & Clark, 2006) based on knowledge acquisition. Secondly, by means of relational learning approaches, it is mainly determined by constructivist notions of sensemaking, which emphasise the relational aspects of learning within communities of practice (Bogenrieder & Nooteboom 2004;Colley, James, Diment & Tedder 2003;Wenger, 1998;Farnsworth, Kleanthous & Wenger-Trayner, 2016), translated into transformative learning (Mezirow, 1997(Mezirow, , 2018 according to the reflexive practices (Alvesson, 2001;Spicer, Alvesson & Kärreman, 2016), and practice-based systemic orientation (Fenwick, 2008(Fenwick, , 2014. And, finally, by means of the complexity theory, it seeks to understand how activities, knowledge and communities work together in the process of workplace learning (Fenwick, 2008;Fenwick & Dahlgren, 2015).…”
Section: Workplace Learningmentioning
confidence: 99%
“…For critical scholars, who seek not only to produce theoretical knowledge but also have ambitions to change organizational theory and practice (Fournier and Grey, 2000) in ways which are emancipating (Alvesson and Willmott, 1992) (Voronov, 2005), divorced from everyday struggles (Bailey and Ford, 1996), stuck within the ivory tower (Parker, 2002;Parker et al, 2007), To remedy this situation a 'performative turn' as demonstrated by 'critical performativity' has been offered as a positive, affirmative, engagement by critical academics with practice rather than a negative critique at a distance (Spicer et al, 2009;Spicer et al, 2016). In this light critical scholars are called on to work with a range of groups such as sweatshop workers (Boje, 1998), trade union and women's groups (Fournier and Grey, 2000), 'social and environmental activists, the unemployed and precarious workforce' (Fleming and Banerjee, 2016 p. 270) and a range of alternative organizations (Kieser and Leiner, 2012), particularly members of NSM (Reedy and Learmonth, 2009;Reedy et al, 2016;Willmott, 2008) or workers cooperatives (Heras-Saizarbitoria, 2014;Paranque and Willmott, 2014) that might offer a more positive vision of organizational practice (King and Learmonth 2015).…”
Section: Engaged Scholarshipmentioning
confidence: 99%